2007
DOI: 10.1007/s00493-007-0047-0
|View full text |Cite
|
Sign up to set email alerts
|

The Erdős–Pósa Property For Long Circuits

Abstract: We show that, for every l, the family F l of circuits of length at least l satisfies the Erdős-Pósa property, with f (k) = 13l(k−1)(k−2)+(2l+3)(k−1), thereby sharpening a result of C. Thomassen. We obtain as a corollary that graphs without k disjoint circuits of length l or more have tree-width O(lk 2 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
132
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(134 citation statements)
references
References 8 publications
(11 reference statements)
0
132
0
2
Order By: Relevance
“…As in [2], a path between two vertices x and y of C that is internally disjoint from C is Proof of Claim A. Let P be a long path between two vertices x and y of C. Let L P denote the length of P. We may assume that C[x, y] is at least as long as C [y, x].…”
Section: Lemma 4 Let G Be a Graph Containing No Two Disjoint Long CImentioning
confidence: 96%
See 1 more Smart Citation
“…As in [2], a path between two vertices x and y of C that is internally disjoint from C is Proof of Claim A. Let P be a long path between two vertices x and y of C. Let L P denote the length of P. We may assume that C[x, y] is at least as long as C [y, x].…”
Section: Lemma 4 Let G Be a Graph Containing No Two Disjoint Long CImentioning
confidence: 96%
“…Let F denote the family of circuits of length at least . In [2], Birmelé, Bondy, and Reed show that F has the Erdős-Pósa property with…”
Section: Introductionmentioning
confidence: 99%
“…Finally, asking whether |E(G)| − e-cover C θ 3 (G) ≤ k corresponds to the Maximum Cactus Subgraph. 2 All parameters keep being NP-complete to compute because the aforementioned base cases can be reduced to the general one by replacing each edge by one of multiplicity r − 1.…”
Section: Approximation Algorithmsmentioning
confidence: 99%
“…Erdős and Pósa also showed that the function cannot be improved to o(k log k), and later Simonovits [25] provided a construction achieving the lower bound. The result of Erdős and Pósa has been strengthened for cycles with additional constraints; for example, long cycles [24,4,10,18,5], directed cycles [23,14], cycles with modularity constraints [26,12] or cycles intersecting a prescribed vertex set [15,19,5,12]. Reed [22] showed that the class of odd cycles does not satisfy the Erdős-Pósa property.…”
Section: Introductionmentioning
confidence: 99%